2019
DOI: 10.1371/journal.pmed.1002780
|View full text |Cite
|
Sign up to set email alerts
|

Lipoarabinomannan in sputum to detect bacterial load and treatment response in patients with pulmonary tuberculosis: Analytic validation and evaluation in two cohorts

Abstract: Background Lipoarabinomannan (LAM) is a major antigen of Mycobacterium tuberculosis (MTB). In this report, we evaluated the ability of a novel immunoassay to measure concentrations of LAM in sputum as a biomarker of bacterial load prior to and during treatment in pulmonary tuberculosis (TB) patients. Methods and findings Phage display technology was used to isolate monoclonal antibodies binding to epitopes unique in LAM from MTB and slow-growi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 38 publications
2
42
0
Order By: Relevance
“…has been observed with slow-growing NTM [28,30]. Our data suggest that cross-reactivity is a small problem, if at all, as slow-growing NTM were observed in only 2 out of 47 patients with false-positive results on SILVAMP-LAM (S11 Table).…”
Section: Plos Medicinementioning
confidence: 61%
“…has been observed with slow-growing NTM [28,30]. Our data suggest that cross-reactivity is a small problem, if at all, as slow-growing NTM were observed in only 2 out of 47 patients with false-positive results on SILVAMP-LAM (S11 Table).…”
Section: Plos Medicinementioning
confidence: 61%
“…Prior to analysis, samples were heat treated at 85°C for 10 minutes. The immunoassays for LAM used the same antibodies as FujiLAM in a sandwich immunoassay format employing ECL detection as described in the Supplemental Methods and elsewhere ( 14 , 17 , 36 ). The research team performing EclLAM had no access to all other clinical, demographic, and test data associated with the samples.…”
Section: Methodsmentioning
confidence: 99%
“…There are few studies reporting LAM concentrations in clinical specimens and direct comparisons between different sample types and assays are complicated by the absence of standardized LAM control materials, sample panels, and reference assays. Four recent studies used the same purified LAM material for calibration and similar antibody reagents for immunoassay-based LAM detection (though different detection platforms) and reported LAM concentrations in sputum [33], blood [34,35], and urine [36] in subjects with active pulmonary TB, allowing for a rough comparison of LAM concentration ranges. For sputum, Kawasaki and colleagues showed that an immunoassay with a cut-off of 15 pg/mL detected all smear-positive and 50% of smear-negative TB patients [33] and sputum LAM concentrations ranged from 15.4 pg/mL to 1,869,000 pg/mL (median 5512 pg/mL).…”
Section: Lipoarabinomannan In Active Tb Diseasementioning
confidence: 99%
“…Four recent studies used the same purified LAM material for calibration and similar antibody reagents for immunoassay-based LAM detection (though different detection platforms) and reported LAM concentrations in sputum [33], blood [34,35], and urine [36] in subjects with active pulmonary TB, allowing for a rough comparison of LAM concentration ranges. For sputum, Kawasaki and colleagues showed that an immunoassay with a cut-off of 15 pg/mL detected all smear-positive and 50% of smear-negative TB patients [33] and sputum LAM concentrations ranged from 15.4 pg/mL to 1,869,000 pg/mL (median 5512 pg/mL). LAM concentration in sputum was linearly correlated to colony forming units (CFU) with 1 pg/mL of LAM correlating to 8 CFU/mL, suggesting that one Mtb bacterium contains approximately 125 fg of LAM [33].…”
Section: Lipoarabinomannan In Active Tb Diseasementioning
confidence: 99%
See 1 more Smart Citation